(untitled) (Comprehensive Journal of Science, 2025)
Renewable energy sources have become one of the most important contemporary research issues, and the importance of their use is due to their cleanliness, time ,and relative cheapness depending on their advantages. This research includes studying the theoretical design of the solar heater system, thermal conversion by knowing thermal absorption , and how to heat water inside the solar heater by knowing its types and working mechanism. The heat conversion system is designed using heat exchangers and how to heat water using solar energy using vacuum glass tubes, knowing their advantages . As the system was designed using new and renewable energy, solar energy , this system supplies the solar heater with its energy needs in a smooth but guaranteed way . In this study ,the values of the energy produced by this system were obtained and its cost was determined as follows:- Thermal conversion system for the solar heater . The total heat required is 15.66 kilowatt hours , while the cost of a 300liter solar heater with an area of 4 vsquare meters is 1,350 Libyan dinars . This study has clearly confirmed that the uas of solar energy through both photovoltaic conversion and direct thermal absorption has significant economic returns in the long and medium term . This fact would be ideal in Libya , where these energies are greatly developed and allow for the development of the environment and public life there